Organophosphorus flame retardants - Toxicity and influence on human health - Elżbieta Bruchajzer; Barbara Frydrych; Jadwiga Anna Szymańska (Nofer Institute of Occupational Medicine, 2015)
Organophosphorus flame retardants (flame retardants, FRs) have been used for several decades in many industries, including the production of dyes, varnishes, adhesives, synthetic resins, polyvinyl chloride, hydraulic fluids, plastics and textiles. Their importance in recent times has increased due to i.a., significantly reduced use of polybrominated diphenyl ethers (PBDEs) - persistent organic pollutants, dangerous for the environment. The aim of this study was to review the available literature data concerning phosphorous FRs primarily for neurotoxic, fertility, reproductive and carcinogenic effects. The analysis concerned the following most commonly used substances: tris(2-ethylhexyl)phosphate (TEHP), tris(2-butoxyethyl)phosphate (TBEP), triphenyl phosphate (TPP), tris(2-chloroethyl)phosphate (TCEP), tetrakis(hydroxymethyl)-phosphonium chloride (THPC), tributyl phosphate (TBP), tricresyl phosphate (TCP), tris(2-chloroisopropyl)phosphate (TCPP), tris(1,3-dichloroisopropyl)phosphate (TDCP) and tetrakis(hydroxymethyl) phosphonium sulphate (THPS). In animal studies neurotoxic effects were found after exposure to TBEP, THPC, TBP and TCP, while in humans they were observed only after exposure to TCP. TCEP, THPS, TBP, TCP and TDCP caused disorders in fertility and/or fetal development of animals. Adverse effects on reproduction in humans may be caused by TPP, TCP, and TDCP. In laboratory animals the development of tumors was observed after high doses of TEHP, TCEP, TBP and TDCP. None of these compounds is classified as a human carcinogen. The environmental toxicity of phosphate FRs is low (except for TPP, TCEP and TBEP). They are not stable compounds, in living organisms they are metabolised and quickly excreted. Therefore, they can be used as an alternative to PBDEs. Med. Pr. 2015;66(2):235-264